Iron trioxide / porous carbon heterogeneous composite wave-absorbing material as well as preparation method and application thereof

By combining iron trioxide with imine covalent organic frame material and forming iron trioxide/porous carbon heterostructure through high temperature carbonization, the existing wave absorber loss method and poor loss capacity are solved, and efficient electromagnetic wave absorption and excellent electromagnetic performance are achieved.

CN119569976AActive Publication Date: 2025-03-07DONGHUA UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411542022.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-03-07
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

The existing wave absorber has a single loss method, poor loss capacity, high raw material cost and cumbersome preparation, making it difficult to meet the needs of electromagnetic protection and electromagnetic stealth.

Method used

The iron trioxide/imine-based covalent organic frame composite is used to composite it with ferrite, and the iron trioxide/porous carbon heterostructure absorbing material is formed through high-temperature carbonization, and the impedance matching is adjusted by magnetoelectric coupling to enhance the electromagnetic wave absorption performance.

Benefits of technology

It realizes efficient electromagnetic wave absorption, has excellent impedance matching and electromagnetic loss capabilities, is easy to prepare, has a wide range of raw materials, is resistant to high temperature and corrosion, and is suitable for use under harsh conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569976A_ABST
    Figure CN119569976A_ABST
Patent Text Reader

Abstract

The invention relates to a ferric oxide / porous carbon heterogeneous composite wave-absorbing material as well as a preparation method and application thereof. The ferric oxide provides high magnetic conductivity and saturation magnetization intensity, the porous carbon formed by carbonizing the covalent organic framework with a regular structure can provide high conductive loss, a heterogeneous interface formed by the composite material provides abundant interface polarization, different element compositions provide dipole polarization, and the composite material has high magnetic conductivity and high saturation magnetization intensity. And good electromagnetic coupling enables the antenna to have excellent impedance matching and electromagnetic loss capabilities.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electromagnetic wave protection, and particularly relates to a ferric oxide / porous carbon heterogeneous composite wave absorbing material and a preparation method and application thereof. Background Art

[0002] With the rapid development of electromagnetic technology, the replacement of various electronic components has greatly improved people's quality of life and accelerated social progress. However, electromagnetic pollution caused by electromagnetic technology has become the fourth largest source of pollution. It is not only harmful to human health, but also has a great impact on communication equipment and threatens communication security. Therefore, people have an urgent need for high-performance absorbing materials with the characteristics of "thin, light, wide and strong".

[0003] Traditional ferrite absorbers have high magnetic permeability and saturation magnetization, so they have extremely strong magnetic loss capabilities; carbon-based materials have excellent electrical conductivity, large dielectric constants, and extremely strong dielectric loss capabilities. However, it is difficult for the two types of materials to form a good impedance match, and a single loss mode often cannot bring about high electromagnetic wave attenuation. At present, there is little research on heterostructured ferrite / carbon electromagnetic coupling systems with high wave absorption performance, and research on electromagnetic performance optimization processes has not yet been fully carried out. It is urgent to develop electromagnetic coupling composite materials that are simple to prepare and have good loss performance to meet the needs of electromagnetic protection, electromagnetic stealth, etc. Summary of the invention

[0004] In view of the defects of the prior art, the technical problem to be solved by the present invention is to provide a ferric oxide / porous carbon heterogeneous composite absorbing material and a preparation method and application thereof, so as to overcome the defects of the existing absorbers such as single loss mode, poor loss capacity, high raw material cost and complicated preparation.

[0005] The present invention provides a covalent organic framework material containing an imine group, wherein the structural formula of the covalent organic framework material containing an imine group is:

[0006]

[0007] The invention provides a ferric oxide / imine-based covalent organic framework composite material. The composite material comprises: the imine-based covalent organic framework material and ferrite.

[0008] The ferrite is ferric oxide modified by a silane coupling agent; wherein the mass ratio of the ferrite to the covalent organic framework material containing an imine group is 1:5 to 3:1, and further, the mass ratio is 1:2 to 3:1.

[0009] Preferably, the ferric oxide / imine-based covalent organic framework composite material is composed of ferric oxide modified by a silane coupling agent and 2,4,6-triformylphloroglucinol-p-phenylenediamine covalent organic framework (TpPa-1-COF), which can be recorded as Fe2O3 / COF.

[0010] The silane coupling agent is 3-aminopropyltriethoxysilane (APTES).

[0011] The preparation method of the silane coupling agent-modified ferric oxide comprises:

[0012] (1) ultrasonically treating ferric oxide in ethanol for 0.5 to 3 hours to obtain a mixed solution, wherein the ratio of ferric oxide to ethanol is 100 to 1000 mg: 50 to 500 mL;

[0013] (2) blending the mixture of 3-aminopropyltriethoxysilane and ethanol with the mixed solution of step (1), ultrasonicating for 1.5 to 4 hours, centrifuging, and drying to obtain silane coupling agent-modified ferric oxide; wherein the volume ratio of the total amount of ethanol (the total amount of ethanol in step 1 and step 2) to 3-aminopropyltriethoxysilane is 200:1 to 50:1.

[0014] In the step (2), the centrifugation is performed by using ethanol as a washing solvent, and the complex is centrifuged at 5000-10000 r / min for 5-20 min; and the drying is performed at 90-160° C. for 24-72 h.

[0015] The present invention provides a ferric oxide / porous carbon composite material. The ferric oxide / porous carbon material is made from a raw material containing any of the ferric oxide / imine covalent organic framework composite materials, and is used to obtain a ferric oxide / porous carbon heterostructure absorbing material through high-temperature carbonization.

[0016] The invention provides a ferric oxide / porous carbon composite material as a magneto-electric coupling heterogeneous composite wave absorbing material for electromagnetic wave absorption.

[0017] The present invention provides a method for preparing a composite of ferric oxide / porous carbon material, comprising:

[0018] The modified ferric oxide nanoparticles, aldehyde-containing aromatic compounds and amino-containing aromatic compounds are mixed, and then 1,3,5-trimethylbenzene, 1,4-dioxane and acid solution are added, and after all are dissolved, they are reacted, washed and dried to obtain a ferric oxide / imine covalent organic framework composite material, which is then carbonized at high temperature to obtain a ferric oxide / porous carbon composite material, that is, a ferric oxide / porous carbon heterostructure absorbing material.

[0019] Preferably, the modified ferric oxide nanoparticles, the aldehyde-containing aromatic compound, and the amino-containing aromatic compound are mixed and placed in a Schlenk tube.

[0020] Preferably, the aldehyde-containing aromatic compound is 2,4,6-triformylphloroglucinol; the amino-containing aromatic compound is p-phenylenediamine; and the modified ferric oxide nanoparticles are silane coupling agent-modified ferric oxide.

[0021] Preferably, the mass ratio of the nano-iron trioxide, the aldehyde-containing aromatic compound and the amino-containing aromatic compound is (0-10):(1-3):(1-9); more preferably, the mass ratio is (3-6):(1-2):(1-5).

[0022] Preferably, the volume ratio of 1,3,5-trimethylbenzene, 1,4-dioxane and acid solution added is (1-5):(1-6):(1-3).

[0023] Preferably, the concentration of the acid solution is 1-5 mol / L; and the acid solution is an acetic acid aqueous solution.

[0024] Preferably, the reaction is carried out at 120-150° C. for 48-96 hours; the vacuum drying temperature is 60-120° C. for 20-48 hours.

[0025] The washing is centrifugal washing or immersion washing.

[0026] The process conditions of centrifugal washing are: using tetrahydrofuran as washing solvent, centrifuging the complex at 5000-10000 r / min for 5-20 min; the process conditions of immersion washing are: using acetone for immersion washing at room temperature, and the washing time is 24-72 h.

[0027] Preferably, the high temperature carbonization process parameters are: sintering temperature of 600-1000°C, heating rate of 3-6°C / min, holding time of 1-6h, and the atmosphere is an inert protective gas, such as N2, Ar.

[0028] The invention provides an electromagnetic wave absorbing device, wherein the device contains the ferric oxide / porous carbon composite material.

[0029] The ferric oxide / porous carbon composite material of the present invention can effectively realize electromagnetic wave absorption, wherein the preparation method of the absorption device is: the test component is made by molding, in order to make the prepared ferric oxide / porous carbon composite absorbing powder evenly distributed in paraffin, the paraffin is heated to 90°C to make it in a melted state, and then the absorbing powder prepared in each embodiment is mixed with the melted paraffin (mass ratio is 5:5) and fully ground, and after the paraffin solidifies, the mixture is placed in a mold and pressed into shape. The size specifications of the cylindrical coaxial sample for electromagnetic performance testing are an inner diameter of 3.04mm, an outer diameter of 7mm, and a sample thickness range of 1 to 3mm.

[0030] The present invention provides an application of the ferric oxide / porous carbon composite material in the field of electromagnetic wave absorption.

[0031] The present invention utilizes two aromatic compounds containing amino and aldehyde groups respectively and ferric oxide in an acidic environment, and the aromatic compounds are dehydrated into rings to form a covalent organic framework material containing an imine group, and compounded with ferrite to jointly construct a ferric oxide / imine covalent organic framework composite material. After high-temperature carbonization, a ferric oxide / porous carbon heterostructure composite material is obtained. With ferric oxide as the magnetic loss material and porous carbon as the dielectric loss material, the heterostructure formed by the two effectively adjusts the impedance matching of the composite material, significantly enhances the electromagnetic wave absorption performance, and has extremely high application value in electromagnetic radiation protection.

[0032] Beneficial Effects

[0033] (1) The present invention uses a novel Schiff-based reaction to synthesize a ferric oxide / imine covalent organic framework composite material, and then synthesizes a ferric oxide / porous carbon heterogeneous composite absorber through high-temperature carbonization. This method provides a new idea for synthesizing electromagnetically coupled high-performance absorbers, using aldehyde- and amino-containing aromatic compounds in an acidic environment to dehydrate the aromatic compounds into rings to form imine groups, thereby constructing a covalent organic framework that forms a heterogeneous structure with ferric oxide. After high-temperature carbonization, the covalent organic framework becomes a porous carbon structure, forming a ferric oxide / porous carbon heterogeneous composite absorber.

[0034] (2) The iron oxide of the present invention provides high magnetic permeability and saturation magnetization, the porous carbon formed by carbonization of the covalent organic framework with a regular structure can provide high conductive loss, the heterogeneous interface formed by the composite material provides rich interface polarization, and the different element compositions provide dipole polarization. The good electromagnetic coupling enables it to have excellent impedance matching and electromagnetic loss capabilities. Further regulation of the electromagnetic parameters of the absorber is achieved by adjusting the carbonization temperature. For example, in the present invention, when the mass ratio of the modified nano iron oxide, 2,4,6-triformylphloroglucinol and p-phenylenediamine is 4.28:1.31:1, the iron oxide / porous carbon prepared by heat preservation at 700°C for 2h has a minimum reflection loss of -64.5dB at 15.35GHz when the thickness is 1.72mm, and the absorption bandwidth less than -10dB in the test frequency band 2-18GHz reaches 4.92GHz.

[0035] (3) The heterostructured ferric oxide / porous carbon composite absorbing material synthesized by the present invention is easy to prepare, has a wide range of raw material sources, has high temperature resistance and corrosion resistance, can be used under harsh conditions, has good reproducibility, and is highly controllable. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 X-ray diffraction patterns of the uncarbonized imine-based covalent organic framework prepared in Example 1 and the ferric oxide / imine-based covalent organic framework composite materials of Examples 2-5;

[0037] Figure 2 Fourier transform infrared spectra of the uncarbonized imine-based covalent organic framework prepared in Example 1 and the ferric oxide / imine-based covalent organic framework composite materials of Examples 2-5;

[0038] Figure 3 The following are scanning electron microscope images of imine-based covalent organic frameworks and ferric oxide / porous carbon composite materials prepared in different embodiments; wherein (a) to (e) are scanning electron microscope images of embodiments 1 to 5, respectively;

[0039] Figure 4 This is a characteristic diagram of electromagnetic wave absorption of the imine-based covalent organic framework prepared in Example 1;

[0040] Figure 5 This is a characteristic diagram of electromagnetic wave absorption of the ferric oxide / porous carbon composite material prepared in Example 2;

[0041] Figure 6 This is a characteristic diagram of electromagnetic wave absorption of the ferric oxide / porous carbon composite material prepared in Example 3;

[0042] Figure 7 This is a characteristic diagram of electromagnetic wave absorption of the ferric oxide / porous carbon composite material prepared in Example 4;

[0043] Figure 8 This is the electromagnetic wave absorption characteristic diagram of the ferric oxide / porous carbon composite material prepared in Example 5. DETAILED DESCRIPTION

[0044] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0045] Raw materials: 2,4,6-triformylphloroglucinol (Shanghai Haohong Biotechnology Co., Ltd.), p-phenylenediamine (Shanghai Mairui Biochemical Technology Co., Ltd.), 3-aminopropyltriethoxysilane (Shanghai Mairui Biochemical Technology Co., Ltd.), nano-iron trioxide (Shanghai Aladdin Biochemical Technology Co., Ltd.), 1,3,5-trimethylbenzene (Sinopharm Chemical Reagent Co., Ltd.), 1,4-dioxane (Sinopharm Chemical Reagent Co., Ltd.), glacial acetic acid (Shanghai Lingfeng Chemical Reagent Co., Ltd.).

[0046] Instruments: Fourier transform infrared spectrometer (Thermo Scientific iD7 ATR), X-ray diffractometer (Bruke D8Advance), field emission scanning electron microscope (Regulus 8230), vector network analyzer (R&S ZNB20).

[0047] The preparation method of modified nano-iron trioxide is as follows: 500 mg of ferric oxide is ultrasonically treated in 50 mL of ethanol for 1 hour, mixed with a mixture of 10 mL of ethanol and 300 μL of 3-aminopropyltriethoxysilane, and then ultrasonically treated for 1.5 hours. After ultrasonication, ethanol is used as a washing solvent, the complex is centrifuged at 8000 r / min for 10 minutes, and dried at 100°C for 24 hours.

[0048] Note: The label Fe2O3 / COF involved in the examples, where Fe2O3, refers to the modified Fe2O3.

[0049] Example 1

[0050] 2,4,6-triformylphloroglucinol (63 mg, 0.30 mmol) and p-phenylenediamine (48 mg, 0.45 mmol) were mixed and placed in a 10 mL Schlenk tube, 1,3,5-trimethylbenzene (1.5 mL), 1,4-dioxane (1.5 mL) and acetic acid aqueous solution (3 mol / L, 0.5 mL) were added, and ultrasonicated for 30 min to mix the above mixed powders evenly. Finally, the mixed solution was placed at 120 ° C for 72 h. After the reaction, centrifugal washing was performed, and tetrahydrofuran was first used for centrifugal washing at room temperature at 8000 r / min for 5 min, and washed three times. Then, acetone was used for soaking and washing at room temperature for 48 h, and the solvent was changed 5 to 6 times during the period. After that, it was placed in a vacuum oven at 60 ° C for 24 h to obtain a pure imine-based covalent organic framework, which was recorded as TpPa-1-COF. The sintering was carried out at a sintering temperature of 600°C, a heating rate of 3°C / min, a holding time of 2h, and an atmosphere of N2, which was recorded as COF-600-2h.

[0051] COF structure:

[0052] Example 2

[0053] Modified nano-iron trioxide (20.58 mg), 2,4,6-triformylphloroglucinol (63 mg, 0.30 mmol) and p-phenylenediamine (48 mg, 0.45 mmol) were mixed and placed in a 10 mL Schlenk tube, 1,3,5-trimethylbenzene (1.5 mL), 1,4-dioxane (1.5 mL) and acetic acid aqueous solution (3 mol / L, 0.5 mL) were added, and ultrasonicated for 30 min to mix the above mixed powders evenly. Finally, the mixed solution was placed at 120 ° C for 72 h. After the reaction, centrifugal washing was performed, and tetrahydrofuran was first used for centrifugal washing at room temperature at 8000 r / min for 5 min, and washed three times. Then acetone was used for soaking and washing at room temperature for 48 h, and the solvent was changed 5 to 6 times during the period. After that, it was placed in a vacuum oven at 60 ° C for 24 h to obtain an iron trioxide / imine covalent organic framework composite material, which was recorded as Fe2O3 / COF 2:9 according to the mass ratio. The sintering was carried out at a sintering temperature of 700°C, a heating rate of 3°C / min, a holding time of 2h, and an N2 atmosphere to obtain an iron oxide / porous carbon composite material, which was marked as Fe2O3 / COF 2:9-700-2h.

[0054] Example 3

[0055] The modified nano-iron trioxide (72.03 mg), 2,4,6-triformyl phloroglucinol (63 mg, 0.30 mmol) and p-phenylenediamine (48 mg, 0.45 mmol) were mixed and placed in a 10 mL Schlenk tube, and 1,3,5-trimethylbenzene (1.5 mL), 1,4-dioxane (1.5 mL) and acetic acid aqueous solution (3 mol / L, 0.5 mL) were added, and ultrasonicated for 30 min to make the above mixed powders uniformly mixed. Finally, the mixed solution was placed at 120 ° C for 72 h. After the reaction, centrifugal washing was performed, and tetrahydrofuran was first used for centrifugal washing at room temperature at 8000 r / min for 5 min, and washed three times. Then acetone was used for soaking and washing at room temperature for 48 h, and the solvent was changed 5 to 6 times during the period. After that, it was placed in a vacuum oven at 60 ° C for 24 h to obtain an iron trioxide / imine covalent organic framework composite material, which was recorded as Fe2O3 / COF 3:4 according to the mass ratio. The sintering was carried out at a sintering temperature of 800°C, a heating rate of 3°C / min, a holding time of 2h, and an N2 atmosphere to obtain an iron oxide / porous carbon composite material, which was recorded as Fe2O3 / COF 3:4-800-2h.

[0056] Example 4

[0057] The modified nano-iron trioxide (205.80 mg), 2,4,6-triformyl phloroglucinol (63 mg, 0.30 mmol) and p-phenylenediamine (48 mg, 0.45 mmol) were mixed and placed in a 10 mL Schlenk tube, and 1,3,5-trimethylbenzene (1.5 mL), 1,4-dioxane (1.5 mL) and acetic acid aqueous solution (3 mol / L, 0.5 mL) were added, and ultrasonicated for 30 min to make the above mixed powders uniformly mixed. Finally, the mixed solution was placed at 120 ° C for 72 h. After the reaction, centrifugal washing was performed, and tetrahydrofuran was first used for centrifugal washing at room temperature at 8000 r / min for 5 min, and washed three times. Then acetone was used for soaking and washing at room temperature for 48 h, and the solvent was changed 5 to 6 times during the period. After that, it was placed in a vacuum oven at 60 ° C for 24 h to obtain an iron trioxide / imine covalent organic framework composite material, which was recorded as Fe2O3 / COF 2:1 according to the mass ratio. The sintering was carried out at a sintering temperature of 700°C, a heating rate of 3°C / min, a holding time of 2h, and an N2 atmosphere to obtain an iron oxide / porous carbon composite material, which was recorded as Fe2O3 / COF 2:1-700-2h.

[0058] Example 5

[0059] The modified nano-iron trioxide (308.70 mg), 2,4,6-triformyl phloroglucinol (63 mg, 0.30 mmol) and p-phenylenediamine (48 mg, 0.45 mmol) were mixed and placed in a 10 mL Schlenk tube, and 1,3,5-trimethylbenzene (1.5 mL), 1,4-dioxane (1.5 mL) and acetic acid aqueous solution (3 mol / L, 0.5 mL) were added, and ultrasonicated for 30 min to make the above mixed powders uniformly mixed. Finally, the mixed solution was placed at 120 ° C for 72 h. After the reaction, centrifugal washing was performed, and tetrahydrofuran was first used for centrifugal washing at room temperature at 8000 r / min for 5 min, and washed three times. Then acetone was used for soaking and washing at room temperature for 48 h, and the solvent was changed 5 to 6 times during the period. After that, it was placed in a vacuum oven at 60 ° C for 24 h to obtain an iron trioxide / imine covalent organic framework composite material, which was recorded as Fe2O3 / COF 3:1 according to the mass ratio. The sintering was carried out at a sintering temperature of 800°C, a heating rate of 3°C / min, a holding time of 2h, and an N2 atmosphere to obtain an iron oxide / porous carbon composite material, which was recorded as Fe2O3 / COF 3:1-800-2h.

[0060] like Figure 1 The X-ray diffraction patterns of COF and Fe2O3 / COF composite materials prepared in different embodiments are shown. Figure 1 It can be seen that the diffraction peak at 4.7° is the crystallization peak of the covalent organic framework, and the peak corresponds to the peak of ferric oxide. With the increase of ferric oxide addition, the defects of the covalent organic framework increase, its crystallinity decreases significantly, and the peak height increases. This covalent organic framework with a relatively regular structure and certain crystallinity has high conductivity after carbonization and has strong conductive loss.

[0061] like Figure 2 The Fourier transform infrared spectra of COF and Fe2O3 / COF composite materials prepared in different embodiments are shown. Figure 2 It can be seen that 1580cm -1 1250cm -1 The characteristic peaks at represent the formation of C=C and CN bonds, respectively, proving the synthesis of the covalent organic framework.

[0062] like Figure 3 (a) to (e) are scanning electron microscope images of Examples 1 to 5, respectively. Figure 3 It can be seen that Figure 3 (a) is a scanning electron microscope image of the carbonized material of TpPa-1-COF without the addition of ferric oxide; (b) to (e) form an obvious heterogeneous structure, with nanorods and nanospheres coexisting. And as the amount of ferric oxide added increases, the number of nanosphere morphology structures in the image increases significantly. Figure 4The electromagnetic wave absorption characteristic image of the ferric oxide / porous carbon composite absorbing material prepared in Example 4 is shown. Figure 4 It can be seen. The preparation method of the absorption component is: the test component is made by molding, in order to make the prepared ferric oxide / porous carbon composite absorbing powder evenly distributed in the paraffin, the paraffin is heated to 90°C to make it in a melted state, and then the absorbing powder prepared in each embodiment is mixed with the melted paraffin (mass ratio is 5:5) and fully ground, and after the paraffin solidifies, the mixture is placed in a mold and pressed into shape. The dimensions of the cylindrical coaxial sample for the electromagnetic performance test are 3.04mm inner diameter, 7mm outer diameter, and a sample thickness range of 1 to 3mm. Based on the obtained electromagnetic parameters, the transmission line theorem can be used to calculate and evaluate the electromagnetic wave absorption performance of the prepared sample. Figures 4 to 8 The following are the wave absorption performance diagrams of the materials prepared in Examples 1 to 5. Figure 4 It can be seen that when the thickness of Example 1 is 4.00 mm, the minimum reflection loss is -3.90 dB at 10.80 GHz. Figure 5 It can be seen that when the thickness of Example 2 is 4.50 mm, the minimum reflection loss is -16.38 dB at 7.04 GHz. Figure 6 It can be seen that when the thickness of Example 3 is 1.50 mm, the minimum reflection loss is -22.39 dB at 17.11 GHz. Figure 7 It can be seen that when the thickness of Example 4 is 1.72 mm, the minimum reflection loss is -64.5 dB at 15.35 GHz, and the absorption bandwidth less than -10 dB in the test frequency band 2-18 GHz reaches 4.92 GHz. Figure 8 It can be seen that when the thickness is 5.00 mm, the minimum reflection loss of Example 5 is -17.34 dB at 16.60 GHz. The electromagnetic parameters are regulated by adjusting the carbonization temperature and the ferric oxide content, so that the material achieves excellent electromagnetic wave absorption performance.

Claims

1. A covalent organic framework material containing an imine group, characterized in that: The structural formula of the imine-containing covalent organic framework material is:

2. A ferric oxide / imine-based covalent organic framework composite material, characterized in that: The composite material is a composite of the imine-containing covalent organic framework material according to claim 1 and ferrite.

3. The ferric oxide / imine covalent organic framework composite material according to claim 1, characterized in that: The ferrite is ferric oxide modified by a silane coupling agent; The mass ratio of ferrite and imine-containing covalent organic framework material is 1:5 to 3:

1.

4. A ferric oxide / porous carbon composite material, characterized in that: The ferric oxide / porous carbon material is obtained by high-temperature carbonization using a raw material containing the ferric oxide / imine-based covalent organic framework composite material according to any one of claims 2-3.

5. A method for preparing a composite of ferric oxide / porous carbon material, comprising: The modified ferric oxide nanoparticles, aldehyde-containing aromatic compounds and amino-containing aromatic compounds are mixed, and then 1,3,5-trimethylbenzene, 1,4-dioxane and acid solution are added, reacted, washed and dried to obtain a ferric oxide / imine-based covalent organic framework composite material, and then high-temperature carbonization is performed to obtain a ferric oxide / porous carbon composite material.

6. The preparation method according to claim 5, characterized in that: The aldehyde-containing aromatic compound is 2,4,6-triformylphloroglucinol; the amino-containing aromatic compound is p-phenylenediamine; and the modified ferric oxide nanoparticles are silane coupling agent-modified ferric oxide.

7. The preparation method according to claim 5, characterized in that: The mass ratio of the modified nano-ferric oxide, the aldehyde-containing aromatic compound and the amino-containing aromatic compound is (0-10):(1-3):(1-9); the volume ratio of the added 1,3,5-trimethylbenzene, 1,4-dioxane and the acid solution is (1-5):(1-6):(1-3); the concentration of the acid solution is 1-5 mol / L; and the acid solution is an acetic acid aqueous solution.

8. The preparation method according to claim 5, characterized in that: The reaction is carried out at 120-150°C for 48-96h; the vacuum drying temperature is 60-120°C for 20-48h; The high temperature carbonization process parameters are: sintering temperature of 600-1000°C, heating rate of 3-6°C / min, holding time of 1-6h, and the atmosphere used is at least one of N2 and Ar.

9. An electromagnetic wave absorbing device, characterized in that: The device contains the ferric oxide / porous carbon composite material according to claim 4.

10. Use of the ferric oxide / porous carbon composite material according to claim 4 in the field of electromagnetic wave absorption.

Citation Information

Patent Citations

  • Bimetallic-organic-framework-based derived porous carbon / multi-wall carbon nanotube nano composite absorbing material and preparation method thereof

    CN108834389A

  • Porous crystalline frameworks, process for the preparation therof and their mechanical delamination to covalent organic nanosheets (CONS)

    US20150266885A1